El burlador de Sevilla (Videoantología de la literatura española, 1994)
The legend of Don Juan who at the height of his licentious career, seduces a girl of noble family and kills her father. Later, seeing a statue on the father's tomb, he flippantly invites it to dine with him. He is dragged down to hell, refuses to repent, and falls to eternal damnation.